Synthesis and self-assembly studies of glycoside surfactants and chromonics / Faramarz Aliasghari Sani - Sani, Faramarz Aliasghari (2012)
This thesis focused on the synthesis and self assembly studies of compounds involving carbohydrates. Two different types of materials were studied, i.e. surfactants and chromonics. Physical investigations of the compounds were conducted by TGA, DSC, OPM, UV-Vis spectroscopy, 1H NMR and surface tension measurements. Sugar-based surfactants are interesting compounds for pharmaceutical and personal care products. Current commercially available surfactants such as alkyl poly glucoside surfactants (APGs) are prepared from low miscibility of sugars and fatty alcohols. In order to solve the miscibility problems of the starting materials, homogenizers are required. This, however, leads to impurities in products, which affects the use of the surfactant for life science applications. Therefore, this work focused on an economic preparation of pure glycoside surfactants. The synthesis approach applied a separation of glycosides and a coupling of sugar and fatty alcohols with different length and chain branching by click chemistry. Twenty one alkyl triazole glycoside surfactants (ATGs) were prepared with more than 80% yield. Twelve of these were anomeric pure products (>95% purity) and nine were technical products of α/ anomeric mixtures. The materials were characterized for their liquid crystal behaviours. Contact penetration studies showed a whole range of lyotropic phases from lamellar to cubic and hexagonal. ATGs’ CMCs were found to be lower than those of APG surfactants. An increase in their chain length meant a decrease in CMC values. Hence these materials could be identified for oil-based surfactants applications.